Success and Safety of Plastic Stent for Endoscopic Ultrasound Guided Pancreatic Pseudocyst Drainage - A Tertiary Single Centre Experience - Khattak, Muhammad Bilal; Khan, Zoya Ali; Khan, Uzair Ali; Ali Khan, Rao Saad; Shabbir, Khawar; Chauhadry, Qurat-ul-Ainy (Pakistan Armed Forces Medical Journal, 2026)
Objective:  To determine the success and safety of plastic stent for endoscopic ultrasound (EUS) guided pancreatic pseudocyst (PP) drainage.Study design: Quasi-experimental studyPlace and duration: Pak-Emirates Military Hospital Rawalpindi, Pakistan from Jan 2018 to Jan 2021Methodology: This study was conducted on seventy three participants with 20-80 years age, both genders, and symptomatic PP.  Cases having small asymptomatic PP (